Oszukańcze oznaczenie towarów i usług w świetle art. 10 ustawy o zwalczaniu nieuczciwej konkurencji - Tylec, Grzegorz (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: This article focuses on issues concerning legal protection of marks – features identifying goods and services in commercial trade. Adopting another partyis mark without their consent or using a similar one may result in infringment of fair competition rules. Hence, the present paper deals with the issue of the protection of marks regulated in article 10 of the law on unfair competition.